Turning around at-risk school: What effective principals do - Md Nor, Sharifah; Roslan, Samsilah (National Dropout Prevention Center, 2009)
At-risk schools are defined by the Department of Education in the state of Selangor, Malaysia as schools with serious disciplinary problems and low academic achievement. In 2003, the Selangor Department of Education identified 22 schools in this category (Selangor State Department of Education, 2003). Some have shown remarkable improvements and have turned around the situation from being "at-risk" to "excellent." This paper is based on a qualitative study of two selected turn-around at-risk schools, one in the State of Selangor and the other in the Federal Territory of Kuala Lumpur, Malaysia. Both had been listed as at-risk by the education department, but are now considered as exemplary due to their accomplishments in various endeavors. In this paper, the authors describe and discuss what principals in these schools did to change the climate of their schools into a positive one that enabled them to turn around their at-risk schools to schools deemed as excellent.